Islamic Ecological Parenting for Sustainable Education: Nurturing Muslim Diaspora Children in Australia - Maulidya Ulfah; Diah Andika Sari; Libri Rizka Puri Windarta; Ayu Luhanarky (Atfaluna: Journal of Islamic Early Childhood Education, 2026)
Purpose – This study aims to examine the influence of Islamic ecological parenting on the sustainable education of Muslim diaspora children in Australia. Sustainable education in this study encompasses the cultivation of Islamic values, the development of environmentally responsible behaviours, and the enhancement of children's spiritual and social awareness within a multicultural context. Design/methodology/approach – A quantitative research approach with a descriptive explanatory survey design was employed. The study involved 170 Muslim diaspora parents with children aged 5–6 years residing in Sydney, Melbourne, and Queensland, Australia. Data were collected through a structured online questionnaire and analyzed using Structural Equation Modelling–Partial Least Squares (SEM-PLS). Findings – The findings indicate that Islamic ecological parenting has a positive and statistically significant effect on children's sustainable education, with the structural model demonstrating substantial explanatory power. Core Islamic values, including trustworthiness (amanah), cleanliness (taharah), balance (mizan), compassion for all living beings (rahmah), and responsibility as stewards of the Earth (khalifah), significantly contribute to fostering sustainable behaviours from an early age. These findings highlight the strategic role of Muslim diaspora families as the primary educational environment for nurturing sustainability values grounded in Islamic teachings. Research implications/limitations – The study is limited to Muslim diaspora families with young children in three Australian states, which may restrict the generalizability of the findings to other age groups or cultural contexts. Future research is encouraged to include broader geographical coverage, longitudinal designs, and cross-cultural comparisons to further validate and extend these findings. Practical implications – The findings suggest that integrating Islamic ecological parenting into family education can strengthen children's environmental awareness, moral development, and sustainability-oriented behaviours. The study provides practical guidance for parents, educators, and policymakers seeking to promote sustainability education through faith-based parenting practices in multicultural societies. Originality/value – This study contributes to the literature by introducing and empirically validating Islamic ecological parenting as a significant predictor of sustainable education among Muslim diaspora children. It offers a novel perspective on how Islamic values can be integrated into sustainability education and provides both theoretical and practical insights for promoting environmentally responsible and socially conscious future generations in multicultural settings.